2015
DOI: 10.1161/hypertensionaha.114.04582
|View full text |Cite
|
Sign up to set email alerts
|

Indexes of Aortic Pressure Augmentation Markedly Underestimate the Contribution of Reflected Waves Toward Variations in Aortic Pressure and Left Ventricular Mass

Abstract: Abstract-Although indexes of wave reflection enhance risk prediction, the extent to which measures of aortic systolic pressure augmentation (augmented pressures [Pa]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…22,26,28 Late systolic load from wave reflections has been shown to induce LV hypertrophy and fibrosis in rats. 26 Accordingly, a relationship between reflection magnitude and LV mass measured with cardiac magnetic resonance imaging has been reported in community-based studies, 47,48 and changes in wave reflection magnitude occurring during antihypertensive therapy are associated with the regression of LV mass independently of the reduction in blood pressure. 27 Wave reflection also plays a role in diastolic dysfunction.…”
Section: Effect Of Wave Reflections and Late Systolic LV Load On Lv Rmentioning
confidence: 88%
“…22,26,28 Late systolic load from wave reflections has been shown to induce LV hypertrophy and fibrosis in rats. 26 Accordingly, a relationship between reflection magnitude and LV mass measured with cardiac magnetic resonance imaging has been reported in community-based studies, 47,48 and changes in wave reflection magnitude occurring during antihypertensive therapy are associated with the regression of LV mass independently of the reduction in blood pressure. 27 Wave reflection also plays a role in diastolic dysfunction.…”
Section: Effect Of Wave Reflections and Late Systolic LV Load On Lv Rmentioning
confidence: 88%
“…In agreement with Hashimoto's findings. a relationship between reflection magnitude (approximated from measured pressure and an assumed physiologic flow waveform) and LV mass has been reported in large community-based studies that included normotensive and hypertensive individuals [15, 24]. Similarly, Quail et al recently demonstrated that in patients with repaired aortic coarctation, reflection magnitude assessed from the ascending aortic distension waveform (a surrogate of the aortic pressure waveform) and measured aortic flow (using phase-contrast MRI) was independently associated with LV hypertrophy [25].…”
Section: Arterial Load and The Left Ventricular Loading Sequence: Rolmentioning
confidence: 99%
“…The present study design has previously been described. 20,[27][28][29][30] Briefly, families of black African descent (Nguni and Sotho chiefdoms) with siblings older than 16 years of age were randomly recruited from the South West Township (SOWETO) of Johannesburg, South Africa. An age threshold of 16 years was employed to avoid the confounding effects of the rapid age-related increase in BP that occurs in younger individuals.…”
Section: Study Participantsmentioning
confidence: 99%
“…[13][14][15] Therefore, more recently, aortic reflected wave function has been determined from reflected wave pressures (Pb) or the reflected wave index (RI) derived from wave separation analysis. [16][17][18][19][20] In this regard Pb or RI have similarly been demonstrated to predict cardiovascular damage beyond brachial BP. [16][17][18][19][20] As indexes of aortic pressure augmentation [3][4][5][6][7] or wave reflection [16][17][18][19] predict risk beyond brachial BP, the factors that determine these variables are of interest.…”
mentioning
confidence: 99%